Socio-economic impact and acceptance study of drone-applied pesticide on maize in Ghana - Annor-Frempong, Festus; Akaba, Selorm (Technical Centre for Agricultural and Rural Cooperation, 2020)
The general consensus among agricultural stakeholders is that smallholder farmers need to become more productive and profitable on a sustainable basis. Unmanned aerial system (UAS) – or drone-based system – services can contribute towards these goals by bringing some of the tools of digital agriculture to agribusiness enterprises, including large and medium-scale holdings, and associations of small-scale farmers growing the same crop on contiguous areas. In Africa, UAS services can be described as nascent and are usually provided by entrepreneurs who invest in the equipment and necessary skills to use the technology, and go on to conduct or sub-contract data analysis, interpret the findings and advise customers. Cutting edge use of specially designed drones allows the devices to be used for agrochemical application on crops.